Brokers, bagmen, and moles fraud and corruption in the Chicago futures markets - Greising, David 1960- (John Wiley & Sons, 1991)
Describes the two year government undercover operation investigating corruption and illegal practices in the two Chicago commodity exchanges and culminating in the indictments of 46 industry professionals.